The inventions and diffusion of hyperinflatable currency - Dror Goldberg (Bar-Ilan University, Department of Economics, 2009)
Paper money, when discretionally issued by a government, can be a very powerful political and economic tool. Who invented it and who caused its global diffusion? Scholars are quick to claim the precedence of their home countries without justifying their claims or contesting competing claims. I comprehensively examine the monetary and public nature of the candidate currencies and the transmission of information about paper currency inventions between countries and across time. I conclude that it was invented independently a few times and its global diffusion began in Canada in 1685.
Keywords: E42; N11; 330; government-issued money; card money; paper money